High-temperature (HT) LiCoO2 recycled from spent lithium ion batteries as catalyst for oxygen evolution reaction. (February 2019) - Pegoretti, V.C.B.; Dixini, P.V.M.; Magnago, L.; Rocha, A.K.S.; Lelis, M.F.F.; Freitas, M.B.J.G.
Graphical abstract: HT LiCoO2 synthesized using the cathodes of LIBs as raw materials as catalyst for OER. Highlights: Thermal synthesis of HT LiCoO2 from Co(OH)2 recycled from spent Li-ion batteries. HT LiCoO2 is used as an electrocatalyst for the oxygen evolution reaction. Cyclic voltammetry and chronoamperometry tests of HT LiCoO2 for OER. The activation free energy of the reaction of OER. Abstract: Development of novel materials based on inexpensive metals is crucial for renewable energy storage technologies. Furthermore, the recycling of compounds, such as lithium cobaltate (LiCoO2 ) from Li-ion battery cathodes, contributes to the recovery of important elements, such as Co and Li. The applicability of high-temperature (HT) LiCoO2 as a multifunctional material has been tested. In this work, HT LiCoO2 is used as an electrocatalyst for the oxygen evolution reaction (OER). Cyclic voltammetry and chronoamperometry tests show that the evolution of oxygen starts at 0.35 V accompanied by the formation of Co 4+ ions. The activation free energy of the reaction calculated using Tafel plot is 28.0 kJ mol −1 and electrochemical impedance spectroscopy elucidates an equivalent circuit with a transfer charge resistance of 1.55 Ω, Warburg impedance of 150.3 Ω, and constant phase elements of 3.50 and 1.35 m F inside the pores and at the double layer, respectively.